(untitled) (Journal of Advanced Research in Social Sciences, 2022)
Tourism is considered an important factor that generates a feeling of satisfaction and wellbeing and contributes to subjective wellbeing and quality of life. The magnificent nature and cross-cultural understanding that tourists have never experienced bring a wider perspective to tourists. In addition, tourism development generates economic growth by increasing foreign exchange income and creating employment opportunities. The rapid growth of tourism has led to the challenge of overtourism as well as conflicts between tourists and residents over the inconvenience caused to residents and the damage caused to the cultural environment due to the cultural differences between the two groups. This phenomenon is relatively more evident at the popular tourist destinations and has aggravated as the number of tourists has grown. This research aims to define the state of overtourism at famous tourist destinations in Japan and classify the level of overtourism based on social media data, primarily from Twitter. As Kyoto is suffering from overtourism, we conduct a comparative study of four other tourist destinations with Kyoto and explore the state of overtourism based on positive and negative expressions collected during January 8 to April 18, 2020. The results show the degree of overtourism for tourism destinations can be classified by the ratio of positive and negative expressions in tweets.